Análisis del discurso publicitario de las academias preuniversitarias en las regiones Cusco y Ayacucho - Paredes Ramírez, Ivonne Alessandra (2020)
For many high school graduates, pre-university academies are the necessary path to take to secure a college vacancy. The purpose of this work is to analyze the discourse that these academies handle through the advertisements they show on the social network Facebook, as well as to make a description of the discursive strategies present in these advertisements.